Adsorption behaviors and mechanisms by theoretical study of herbicide 2,4,5-Trichlorophenoxyacetic on activated carbon as a new biosorbent material - Naboulsi, A.; El Mersly, L.; Yazid, H.; El Himri, M.; Rafqah, S.; El Haddad, M. (Journal of the Taiwan Institute of Chemical Engineers, 2023)
•Low-cost carbon – adsorbent was prepared from the stems of Ritama-Monosperma (L.) Boiss Wood as a new bioserbent by chemical activation and carbonation.•The surface of the activated carbon is full of carboxylic acid (300 mmol/g), determined by Boehm titration.•The maximum capacity of CA-P 24.178 mg/g was achieved.•A theoretical study by DFT determined the adsorption mechanism of 2,4,5-Trichlorophenoxyacetic herbicides from aqueous. Adsorption remediation is a low-energy water treatment technology based on removing different types of pollutants using the adsorption properties of a biosorbent. However, the biosorption of the pesticide 2,4,5-Trichlorophenoxyacetic on a plant named Ritama-Monosperma (L.) Boiss carbonized and activated by phosphoric acid as a new potential modern and eco-friendly biosorbent is the subject of this work. The characteristics of the biosorbent are then determined utilizing several structural and textural characterization techniques such as XRD, FTIR, SEM/EDX, pHzpc, and Boehm titration. Batch adsorption tests were performed to investigate the impact of various parameters. However, the Freundlich, Languemir, Temkin, and Dubinin-Radushkevich models were employed to examine the experimental isotherm data. The density functional theory (DFT) modeling of 2,4,5-Trichlorophenoxyacetic has allowed us to discover the origin of the reactivity. According to biosorption kinetic data, the elimination of 2,4,5-Trichlorophenoxyacetic followed a pseudo-second-order response with a maximum adsorption capacity of 24.17 mg/g. The generalized isotherms demonstrated that the Freundlich isotherm best fitted the equilibrium data. The Thermodynamic study shows that pesticide biosorption is exothermic, spontaneous, and represents a decrease in randomness at the adsorbent-adsorbate interface, which is regulated by physisorption and happens as a result of electrostatic interactions, between the positively charged carbon surface at pH below 2.5, and the most nucleophilic centers C2, C5, C15, according to theoretical calculations, and pHzpc analysis. [Display omitted]